2020
DOI: 10.3389/fnut.2020.600215
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Potential of the Native Australian Green Plum (Buchanania obovata) Compared to Other Anacardiaceae Fruit and Nuts

Abstract: The native Australian green plum (Buchanania obovata) is a small fruit that grows in the northern parts of the Northern Territory and Western Australia. The fruit belongs to the family Anacardiaceae, which includes the other agriculturally important fruit mangoes, pistachios and cashew nuts. The green plum is a favored species of fruit for the Aboriginal communities and an important bush food in the Northern Territory. To date, only minimal scientific studies have been performed on the green plum as a food. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 82 publications
(104 reference statements)
0
13
0
2
Order By: Relevance
“…[26] Previous research has demonstrated that diets high in fiber can enhance satiety and inhibit appetite, which may result in decreased energy intake and weight loss. [27] The possible mechanism is that dietary fiber can be fermented by gut bacteria to produce short-chain fatty acids (SCFAs), which increases the production of satiety to control weight by regulating the production of gut hormones such as peptide YY (PYY) and glucagon-like peptide -1 (GLP-1). [28] Similarly, the current study indicated that maternal weight gain during the intervention was significantly lower in the dietary fiber group compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Previous research has demonstrated that diets high in fiber can enhance satiety and inhibit appetite, which may result in decreased energy intake and weight loss. [27] The possible mechanism is that dietary fiber can be fermented by gut bacteria to produce short-chain fatty acids (SCFAs), which increases the production of satiety to control weight by regulating the production of gut hormones such as peptide YY (PYY) and glucagon-like peptide -1 (GLP-1). [28] Similarly, the current study indicated that maternal weight gain during the intervention was significantly lower in the dietary fiber group compared to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Problems like tonsillitis, skin boils, eye diseases, stomach ache, common cold, and eczema are treated by the consumption of this plant and it also acts as a laxative, diaphoretic, and diuretic. It is also a component of traditional medicine as an expectorant, antispasmodic, anti‐exudate, antidepressant, and anti‐inflammatory (Fyfe et al, 2020). The aerial portion of B. perennis is usually consumed as a vegetable.…”
Section: Edible Flowersmentioning
confidence: 99%
“…O país registra quantidade expressiva de gêneros e espécies da família, Albuquerque et al (2015) destacaram que a busca por compostos fenólicos, substâncias bioativas e metabólitos secundários em espécies do táxon tem sido objeto de diversas pesquisas no campo químico o que justificaria a quantidade de publicações. Além disto, a produção e valoração econômica da família também se destaca como fator importante para realização destas publicações (Fyfe et al, 2020;Lacaris et al, 2019;Oliveira et al, 2018). Raddi, que ocorre no Japão (Morishige, 1940).…”
Section: Prospecção Científicaunclassified